Non-obstetric surgery during pregnancy - an eleven-year retrospective analysis - J. Vujic; K. Marsoner; A. H. Lipp-Pump; P. Klaritsch; H. J. Mischinger; P. Kornprat (BMC, 2019)
Abstract Background Diagnosis and management of non-obstetric abdominal pathologies during pregnancy are clinically challenging for both obstetricians and general surgeons. Our aim was to evaluate the outcome of pregnant patients who had undergone non-obstetric abdominal surgery. Methods We retrospectively reviewed 76 pregnant patients who had required surgery for non-obstetric abdominal pathologies during pregnancy at our department from January 2005 to December 2015. Data were collected retrospectively from medical records as well as from our institutional perinatal database. We evaluated data for clinical presentation, perioperative management, preterm labor, and maternal and fetal outcomes. Results The patients' mean age was 29 (interquartile range IQR 25-33) years. Indications for surgery were acute appendicitis in 63%, adnexal pathology in 11%, cholecystolithiasis in 5% and other indications in 21%; surgery was performed in an elective setting in 18% and in an emergent/urgent setting in 82%. In five cases, complications, three of them oncological, called for further surgery. Ninety-seven percent of operations were conducted under general anesthesia. Median skin-to-skin time was 50 (37-80) minutes, median in-hospital stay was 4 (3.5-6) days, and 5 % required postoperative intensive care. Preterm labor occurred in 15%, miscarriage in 7% (none of them directly related to abdominal surgery). Conclusion Abdominal surgery for non-obstetric pathology during pregnancy can be performed safely, if mandatory, without increases in maternal and fetal pathology, miscarriage, and preterm birth rates.